HYPERTHYROIDISM AND GRAVES’ DISEASE: OPHTHALMOLOGICAL MANIFESTATIONS AND SURGICAL TREATMENT. - Santos, Luan Bernardino Montes; Costa, Thelma da; Barros, Layla Azevedo Alencastro Cupertino de; Almeida, Pedro da Costa Siqueira de; Oliveira, Gabriel Nojosa; Amaro, Lara Lacerda; Cruz, Rayane Alves; Alencar, Dayanne Soares; Rodrigues, Matheus do Carmo; Correa, Stefanny Machado; Martins, Pedro Felipe Rezende; Ribeiro, Pedro Henrique Rodrigues (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Hyperthyroidism, characterized by the excessive production of hormones by the thyroid gland, can lead to various systemic complications, including ophthalmological manifestations such as Graves’ Orbitopathy (GO). Graves’ Disease, one of the main causes of hyperthyroidism, is often associated with these ocular complications, which include ocular protrusion, diplopia, and periorbital swelling. Surgical treatment, including total or subtotal thyroidectomy, emerges as an option to control the progression of hyperthyroidism and improve associated ophthalmological symptoms. **Objective**: To analyze the ophthalmological manifestations of hyperthyroidism and Graves’ Disease, as well as evaluate the effectiveness of surgical treatment in managing these complications. **Methodology**: The review followed the PRISMA checklist to ensure rigor and transparency. Searches were conducted in PubMed, Scielo, and Web of Science databases using five descriptors: "Hyperthyroidism," "Graves’ Disease," "Graves’ Orbitopathy," "Surgical Treatment," and "Ophthalmological Manifestations." Inclusion criteria encompassed articles published in the last 10 years, studies focused on surgical treatment for GO, and works explicitly addressing the ophthalmological manifestations of Graves’ Disease. Exclusion criteria included studies that did not discuss surgical treatment, non-peer-reviewed articles, and publications older than a decade. **Results**: The analysis revealed that Graves’ Orbitopathy frequently manifests with symptoms such as ocular protrusion, diplopia, and periorbital edema, significantly impacting patients’ quality of life. Thyroidectomy proved effective in reducing hormone levels, resulting in symptomatic improvements for many patients. However, outcomes varied, and surgical intervention was not always associated with complete resolution of ophthalmological manifestations. **Conclusion**: Surgical treatment of hyperthyroidism and Graves’ Disease can provide significant relief from ophthalmological manifestations, though it does not guarantee complete resolution of symptoms. Surgery should be considered within a multidisciplinary context, taking into account the severity of ocular symptoms and response to conservative treatment. The review highlighted the need for integrated treatment strategies to optimize outcomes for patients with ophthalmological complications associated with hyperthyroidism and Graves’ Disease.